Efficacy of Vitamin D Combined with Metformin and Clomiphene in the Treatment of Patients with Polycystic Ovary Syndrome Combined with Infertility - Lili ZHUANG; Wei CUI; Jianxiang CONG; Yinghong ZHANG (Tehran University of Medical Sciences, 2019)
Background: We aimed to explore the clinical efficacy of vitamin D combined with metformin and clomiphene in the treatment of patients with polycystic ovary syndrome combined with infertility. Methods: Overall, 396 cases of polycystic ovarian syndrome combined with infertility in Yantai Yuhuangding Hospital, Yantai, China were prospectively analyzed. Among them, 204 cases treated with vitamin D combined with metformin and clomiphene were set as the study group; 192 cases treated with only metformin and clomiphene were set as the control group. The ovarian volume and thickness of uterine wall before and after treatment were recorded. Levels of fasting insulin (FINS), luteinizing hormone (LH), testosterone (T), follicle-stimulating hormone (FSH), and estradiol (E2) before and after treatment were recorded. Results: There was no difference in body weight, BMI, ovarian volume, thickness of ovarian wall, FINS, LH, T, FSH and E2 between the study group and the control group; there was no significant difference in FSH, E2 and the thickness of uterine wall between the two groups. After treatment, the BMI, FINS, LH, and T in the study group were significantly lower than those in the control group (P<0.05); the incidence rates of oligomenorrhea, facial acne and hairy symptoms in the study group were significantly lower than those in the control group (P<0.05); after treatment, the ovulation rate and pregnancy rate in 36 cycles in the observation group were significantly higher than those of the control group (P<0.05). Conclusion: Our challenge could significantly improve clinical symptoms and endocrine conditions, and greatly enhance the ovulation rate and pregnancy rate.